Edukasi Pencegahan Anemia dan Pemeriksaan Kadar Haemoglobin Pada Remaja Putri di Lingkungan Ciherang Kelurahan Linggasari - Dewi, Sri Wulan Ratna; Ariani, Dini; Septiani, Hani; Nurherliyany, Metty; Mutmainah, Nida Nadiatul (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Introduction : Anemia in adolescent girls and its various impacts are still a national and regional problem. Health education activities through a combination of lecture methods with leaflet media and checking HB levels in adolescents are still one of the solutions to prevent and overcome the problem of anemia in adolescent girls through increasing knowledge and awareness of adolescent girls regarding the importance of fulfilling nutrition during adolescence. Objective : This community service aims to provide education to adolescents directly and can check Haemoglobin (Hb). Methods : The method used in the Anemia Prevention education activity is a lecture using E-Leaflet media and also checking HB levels in adolescent girls. Results : This activity was significant in providing adolescents with an understanding of anemia, how to overcome anemia, and how to take blood supplement tablets as well as the knowledge of Hb levels, most of which were in the normal category, namely HB levels> 11 gr/dl. Conclusion : Based on the results of Community Service activities, education about anemia to adolescent girls in the Ciherang environment with lecture methods supported by leaflets can increase knowledge about anemia and can determine Hb levels.